Automatic air-cooling system for early-age crack control in concrete. Issue 5 (24th October 2018) - Li, Xiongyan; Geng, Yan; Xue, Suduo; Li, Jinguang; Song, Yanjie; Kang, Guangbo
Abstract : Early-age heat-induced cracking is a potentially fatal problem for critical concrete structures such as liquefied natural gas storage tanks. This paper reports on a novel automatic air-cooling system designed to solve the problem. The system was designed following a series of air-cooling experiments in China on concrete walls during the first 72 h after casting. An air velocity of approximately 12 m/s appears to provide effective cracking control for ambient air temperatures up to 30°C, while the optimal cooling segment length was found to be approximately 14 m. The paper aims to provide a reference for the application of air cooling for any large-scale concrete structures at risk of early-age cracking.